Browning's beginnings : the art of disclosure - Tucker, Herbert F. (University of Minnesota Press, 1980)
Browning?s Beginnings offers a fresh approach to the poet who, among major Victorians, has proved at once the most congenial and most inscrutable to modern readers. Drawing on recent developments in literary theory and in the criticism of romantic poetry,